Aktivitas Antibakteri Kombinasi Ekstrak Etanol Daun Johar (Cassia siamea Lamk.) dan Daun Alpukat (Persea americana Mill.) terhadap Salmonella Typhi - Hanugrah Ardya Crisdian; Kusumaningtyas Siwi A (Jurnal Farmasi Indonesia, 2021)
Typhoid fever is an acute febrile disease caused by Salmonella typhi bacteria, WHO 2018 data states that in the world it reaches 11-20 million cases per year, in Indonesia it reaches a prevalence rate of 358-810/100,000 population. The purpose of this study was to determine the antibacterial activity of the combination of johar leaves (Cassia siamea Lamk) and avocado leaves (Persea americana Mill) against the growth of salmonella typhi bacteria. Testing the antibacterial activity of a combination of 1:1 70% ethanol extract of johar leaves and avocado leaves by diffusion and dilution methods, treatment using control (+) ciprofloxacin and control (-) DMSO 2% with series concentrations of 25, 50, 75 and 100%. Each treatment was repeated 3 times. The results of the antibacterial activity test of the combination of ethanol extract of johar leaves and avocado leaves had the greatest activity against Salmonella typhi bacteria at a concentration of 100% with a clear zone diameter of 9.9 mm while the smallest average was at a concentration of 25% with a diameter of 6 mm, and ciprofloxacin with a diameter of 29.3 mm. The minimum inhibition level was at a concentration of 12.5%.